Infantile Convulsions and Retinal Hemorrhages - J Gordon Millichap (Pediatric Neurology Briefs, 2009)
The prevalence of retinal hemorrhages in infants presenting with convulsions was studied at Hospital Universitari Sant Joan de Deu, Barcelona, Spain.